Konfession, Migration und Elitenbildung: Studien zur Theologenausbildung des 16. Jahrhunderts - Selderhuis, H. J.; Wriedt, Markus (Brill's series in church history, 2007)
The keywords migration, elite, and confession that form the leitmotiv of this book allow a focus on major subjects of research in early modern history. Concentrating on subjects relevant to the history of education, the essays collected here offer manifold insights into new source material and the evaluation of methods. The fifteen papers cover a wide range of topics related to the education of academic theologians and clergy in the sixteenth and seventeenth centuries. As training programmes differed from university to university, this gave rise to migration and an extensive communicative network. Although a final conclusion of methodological questions requires more research, the volume provides an important contribution to the interdisciplinary discussion between representatives of the many historical disciplines. The fifteen contributors: Luca Baschera, Amy Nelson Burnett, Otfried Czaika, Simone Giese, Anja-Silvia Göing, Leonhard Hell, Wim Janse, Julian Kümmerle, Andreas Mühling, Hans Peterse, Frank van der Pol, Sünje Prühlen, Alexander Schunka, Sven Tode, and Jason Zuidema